Mild cognitive impairment: associations with sleep disturbance, apolipoprotein e4, and sleep medications - Burke, Shanna L. (Sleep Med, 2018)
OBJECTIVE: Mild cognitive impairment (MCI) is associated with increased memory problems although the ability to complete daily life activities remains relatively intact. This study examined: (1) if sleep disturbance increased the hazard of MCI; (2) if APOE e4 carriers with sleep disturbance experience an increased risk of MCI; and, (3) if prescription sleep medications provide a protective effect against MCI. We hypothesized that sleep disturbance increases the hazard of MCI, this relationship is stronger among APOE e4 carriers reporting a sleep disturbance. Furthermore, we hypothesized that sleep medications decrease the hazard of MCI. METHODS: To determine whether sleep medication mediates the risk of developing MCI for individuals with sleep disturbance and/or APOE e4, we analyzed the National Alzheimer’s Coordinating Center Uniform Data Set. We selected participants with normal cognition at baseline (n = 6798), and conduced survival analyses. RESULTS: Our main findings indicated that the hazard of MCI was significantly associated with sleep disturbance. The hazard remained among those who did not use sleep medication. Trazodone and zolpidem users did not have a significant hazard of MCI, but the significant hazard remained for those who did not use these medications. APOE e4 carriers had a significantly higher hazard of MCI. Among e4 carriers who used trazodone or zolpidem, there was not a statistically significant risk of MCI. CONCLUSION: This study demonstrated the potential utilization of trazodone and zolpidem in the treatment of sleep disturbance while potentially mitigating the risk of MCI. While trazodone and zolpidem have been shown to positively impact sleep disturbance in individuals with normal cognition, further research should explore these findings given that these medications are potentially inappropriate for older adults.